PERSEPSI GURU DAN ORANG TUA SISWA SEKOLAH DASAR TERHADAP DUNIA KESENIRUPAAN ANAK - Darmaja Giri, I Kadek Agus (Universitas Pendidikan Ganesha, 2010)
The aims of this study were to know (1) The position of fine art subject in the eyes of the elementaryschool students’ teachers and parents; (2) The attention of the teachers and parents to the fine artstudy of the elementary school students; (3) The point of view of the elementary school students’teachers and parents about the relationship between fine art subject and the development of students’aptitude and creativity; (4) The point of view of the elementary school students’ teachers andparents about the relationship between fine art subject and the development of students’ psychology.The point to be discussed in this study was the perception of elementary school students’ teachersand parents toward the fine art study of the students. This study used the descriptive approach, theinstruments of which were questionnaire, observation, interview, and documentation. It also appliedthe Semantic Differentials analysis technique in scaling the questionnaire.The result to be found were as follows: (1) The position of the fine art subject in the eyes of elementaryschool students’ teachers and parents is still at the secondary one compared to the othersubjects, especially those which are tested in the National Final Examination. Its general reason isthat those subjects are very important in determining students’ graduation later; (2) The attentionof the teachers and parents to students’ fine art study are very low; (3) The knowledge of the elementaryschool students’ teachers and parents about the relationship between fine art subject andthe development of students’ aptitude and creativity is very minimum; (4) The point of view of theelementary school students’ teachers and parents about the relationship between fine art subjectand the development of students’ psychology is still so far from what is expected.